Blockchain-based Land Certificate Management in Indonesia - Rosiyati MH Thamrin; Eka Purnama Harahap; Alfiah Khoirunisa; Adam Faturahman; Kenita Zelina (ADI Journal on Recent Innovation, 2021)
Indonesia is a densely populated country with a population of 260 million, making Indonesia the fourth most populous country in the world. The continued rapid development of the economy in Indonesia has made land an asset that provides benefits. In Indonesia, land ownership that has the highest legal power is proven by a Certificate of Ownership or in indonesian is called as Sertifikat Hak Milik (SHM). Meanwhile, the land titling process is often complex and lengthy, and because of the processing carried out by government agencies in handling a variety of different documents, some structured people commit fraud. The impact is that the model currently used does not have good governance. This research offers a Blockchain-based solution in providing data harmony and openness, lightening in data access, permanent records management, and most importantly it is a solution that is cheaper and faster. This research offers a step-by-step model of Blockchain selection beginning from the public Blockchain ledger which will continuously incorporate two degrees of Hybrid Blockchain. The smart contract design of the Public Blockchain is provided in detail as well as the use of Ethereum in implementing its prototype system. In the experimental test using the local Ethereum test network directly to show the effectiveness of the system. The results of the analysis show that the model offered can reduce the costs required for processing information, the number of trips required, and result in easy access to important information. With the implementation of Blockchain, efforts to digitize land rights in Indonesia can increase.